How Do We Look? - Peffer, John (Kronos: Southern African Histories, 2021)
In South Africa under apartheid, portrait images displayed in private homes emphasised the dignity of their subjects and the stability of family life during a period of indignity and social upheaval. But when interviewing families about them, one often encounters sensitivity issues of the sort too often passed over by scholars and curators who valorise studio practices without consulting the actual subjects of the images. These include a range of anxieties about repackaging for display in new contexts and for broader audiences, as well as basic copyright and authorship concerns in common with other African and ‘family’ photographies. The particular anxieties themselves speak to the local histories of how these self-images were used and lived. This essay argues for a closer consideration and a new ethics for looking at and writing about these pictures. It is based on research since 2010 on family collections of photographs in South Africa’s Black urban neighbourhoods.